CONFLICT MANAGEMENT IN ART ORGANIZATIONS: MODERN STRATEGIES FOR CREATIVE COOPERATION AND ORGANIZATIONAL STABILITY (World Bulletin of Education and Learning, 2026)
This article examines modern approaches to conflict management in organizations operating within the sphere of art and culture. The study analyzes the specific characteristics of conflicts in creative environments and evaluates the effectiveness of contemporary conflict-management strategies in maintaining organizational stability and creative productivity. Particular attention is devoted to emotional involvement, artistic disagreements, communication barriers, mediation practices, and leadership approaches in theaters, galleries, museums, and creative studios. The research applies analytical, systemic, and comparative methods to evaluate conflict-resolution models and organizational interaction processes. Research findings demonstrate that effective conflict management significantly improves communication, strengthens organizational culture, reduces emotional tension, and supports sustainable creative cooperation. The article further explores the importance of emotional intelligence, mediation, and adaptive leadership in managing conflicts within modern art organizations.
Keywords: Conflict management, art organizations, creative environment, organizational communication, emotional intelligence, mediation, leadership, organizational culture, creative cooperation, management strategies.